Novel Oral Anticoagulants - Vinall, Maria (MD Conference Express, 2010)
This article discussed some of the novel targets for anticoagulants, the two most immediate of which are Factor Xa and Factor IIa (thrombin), as well as overview of the characteristics of five new anticoagulant agents and current studies that involve these agents.